Manajemen Perparkiran Di UIN Sunan Gunung Djati Bandung - Nurul Anbiya; Putri Mutia Handayani; Rai Galih Muta`ali (Gunung Djati Conference Series, 2023)
Parking management issues are frequently encountered in various universities due to suboptimal land management. Sunan Gunung Djati State Islamic University in Bandung is one such public university that is also not exempt from parking problems. Therefore, this research aims to analyze the implemented parking management system, including its technology, policies, and procedures. The research can help identify the strengths and weaknesses of the current system. The research method that can be employed is descriptive research with a qualitative approach. The data sources include primary and secondary data. Primary data is obtained through interviews with parking management, parking attendants, and users, while secondary data is derived from document studies and observations related to parking management. The findings of this research indicate that several aspects have been analyzed, showing that overall, parking management at UIN Sunan Gunung Djati Bandung has made progress but still requires further attention and support to improve the parking conditions